Polymorphism of clinical phenotypes and heterogeneity of autoimmune targets of myasthenia gravis - Klimova, Olena; Drozdova, Larisa; Lavinska, Olena; Kudrevych, Oleksandr (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2020)
Abstract. The aim of the study was to evaluate the presence of autoantibodies to different subunits of nAChR and nuclear antigens at different myasthenia phenotypes. The work has investigated the presence of antibodies to α1- and α7-subunits of nAChR, the repertoire and frequency of occurrence of antinuclear autoantibodies in different clinical phenotypes of myasthenia to understand the mechanisms of pathogenesis of various forms of the disease. Additional factors of autoimmunization were identified that affect certain mechanisms of pathogenesis in thymus-independent and thymus-dependent myasthenia gravis. Autoantibodies to α1 and α7 subunits of nAChR were detected in case of thymus-independent myasthenia gravis and thymus-dependent myasthenia gravis with thymus hyperplasia or locally spread thymoma, as well as the presence of antinuclear antibodies in case of thymoma on the background of myasthenia gravis. Autoantibodies to the α1 subunit of nAChR are available in all patients with thymus-independent and thymus-dependent myasthenia gravis; the maximum titer was in patients with myasthenia and thymus hyperplasia. The presence of autoimmune antibodies to another target – to the α7 subunit of nAChR was found in patients with thymus-independent myasthenia gravis and with myasthenia and thymus hyperplasia. Detected anti-nuclear antibodies (ANA) in patients with thymoma, are preferably antibodies to structures that are directly involved in mitotic cell division, that is to centromere, to centromeric protein F, to the centrosomal protein of achromatin spindle – NuMa and MSA-2 antigen mitotic spindle that affects the course of cell proliferation, reparative and regenerative processes in tissues. The selectivity of antibody damage by the subunit of NAHR in different myasthenia phenotypes and the presence of ANA in thymus-dependent myasthenia with thymoma has great diagnostic and prognostic value. The presence of specific autoantibodies to certain nuclear structures of the cell, along with other autoimmunization mechanisms, affects various metabolic mechanisms and can be used to select targeted therapy taking into account individual pathogenic targets of the autoimmune process.